USE OF SCIENTIFIC RESEARCH METHODS IN REHABILITATION OF PATIENTS WITH MYOCARDIAL INFARCTION - Abduvaliyev Khusniddin Mirzajon og’li; Dekhkambayeva Zulfiya; Nadirova Yulduz Isomovna (Bright Mind Publishing, 2025)
Myocardial infarction (MI) is one of the most dangerous and deadly cardiovascular diseases, and in addition to saving the patient's life, it is also an important issue to restore their quality of life. From this point of view, the rehabilitation process in the post-infarction period plays a decisive role in restoring cardiac function, improving the physical and psychological condition of the patient, and preventing recurrence of the disease. This scientific article deeply studies the role, importance, and effectiveness of using scientific research methods in the rehabilitation process after myocardial infarction. The study analyzes the use of methods such as clinical observation, functional tests, statistical analysis, experimental methods, psychological assessment tools used in the rehabilitation of patients, their advantages and limitations. At the same time, it highlights the possibilities of assessing the effectiveness of rehabilitation through the use of modern medical technologies (ECG monitoring, Holter, cardiac ultrasound, laboratory indicators). Rehabilitation is carried out in stages (hospital, outpatient and home), and individual approaches are required for each stage. The study substantiates the scientific methods that should be used for each stage. It also analyzes the assessment of the physical condition of patients based on functional tests, the use of "questionnaires for determining the psychological state (e.g. HADS, SF-36)", and the possibilities of mobile technologies for monitoring rehabilitation at home. At the end of the work, it is substantiated that the correct selection of scientific research methods and their integration are important in increasing the effectiveness of rehabilitation, faster recovery of patients' health and reducing the risk of recurrent myocardial infarction. The results of the study can be used in the practical healthcare system, rehabilitation centers and medical universities.
Keywords: Myocardial infarction, rehabilitation, clinical observation, scientific research methods, physical recovery, psychological state, functional tests, cardiac activity, statistical analysis, individual approach, stages of recovery, Holter monitoring, rehabilitation effectiveness, health restoration, cardiovascular system.